Review of the genus Lomachaeta Mickel, 1936 (Hymenoptera: Mutillidae) with new species and sex associations - Williams, Kevin A.; Cambra, Roberto A.; Bartholomay, Pedro R.; Luz, David R.; Quintero, Diomedes A.; Pitts, James P. (Zootaxa, 2019)
New species and sex associations are proposed in the genus Lomachaeta Mickel, 1936. Six new species are described: Lomachaeta calamondin Williams, L. eironeia Williams, L. juanita Williams, L. meloi Williams, L. osita Williams, and L. warneri Williams. The previously unknown females of five species are described: L. beadugrimi (Pitts & Manley, 2004); L. chionothrix Pitts & Manley, 2004; L. hedera Williams & Pitts, 2009; L. hyphantria Pitts & Manley, 2004; and L. vacamuerta Williams & Pitts, 2009. The previously unknown male of L. vianai Casal, 1969 is described and L. megomicron Williams & Pitts, 2009 is placed as its synonym. Various new country and state records are presented. New keys and habitus pictures for all the 24 known species are provided.